Chemical Constituents of Gymnopilus spectabilis and Their Antioxidant Activity - Lee, In-Kyoung (The Korean Society of Mycology, 2008)
Gymnopilus spectabilis, a hallucinogenic mushroom belonging to the family Cortinariaceae, is found growing in dense clusters on stumps and logs of hardwoods and conifers. It contains the hallucinogenic alkaloid psilocybin and its strongly bitter taste makes it undesirable as an edible. In an effort to identify chemical constituents of Korean native wild mushrooms, 4,6-decadiyne-1,3,8-triol (1), ergosta-4,6,8(14), 22-tetraen-3-one (2), bisnoryangonin (3), and hispidin (4) were isolated from the methanolic extract of the fruiting bodies of G. spectabilis. Their structures were assigned on the basis of various spectroscopic studies. Compounds 3 and 4 displayed significant scavenging activity against the ABTS radical cation, DPPH radical, and superoxide radical anion, while 1 and 2 exhibited no antioxidant activity.